Creep investigations on adhesively bonded fasteners developed for offshore steel structures. (January 2020) - Djeumen, E.; Chataigner, S.; Créac'hcadec, R.; Sourisseau, Q.; Quéméré, M.O.; Court, J.P.; Sayed, F.
Abstract: Fastening or reinforcement onto an existing steel structure may create constraints such as the use of hot works (i.e. welding) or loss of weathertightness (i.e. drilling holes and bolting). In order to limit these constraints, there may be a strong interest in using adhesively bonded fasteners. Such a solution requires however strong justification especially regarding long-term properties. This paper presents the results of experimental and numerical investigations realized on the creep behaviour of such bonded fasteners developed for offshore steel structures. Experimental investigations were conducted at room temperature following a precise and repeatable implementation protocol. The results of the various investigations revealed a non-linear evolution of creep displacements according to a Burger law. Numerical modelling has therefore been developed on the basis of Burger's law. A preliminary static study aimed at validating the geometric model and analyzing the initial stress state in the adhesive. The creep study was then carried out to compare numerical results to experimental ones. Although additional investigations are needed, numerically determined creep displacements demonstrated a good consistency with the experimental investigations. Highlights: Adhesively bonded fastener's creep behaviour was experimentally investigated. Creep modelling was undertaken using Burger's approach. Good correlation between experimental investigations and modelling was obtained. An anisotropic behaviour of the adhesive in creep was demonstrated.